Organic polyimide fiber lithium ion battery diaphragm as well as preparation method and application thereof

By using organic polyimide fibers and specific slurries on lithium-ion battery separators, the problem of insufficient performance improvement of existing separators under high film breaking temperature and high performance requirements is solved, and the improvement of high ionic conductivity, tensile strength and film breaking temperature is achieved, while enhancing the adhesive performance.

CN119651042AActive Publication Date: 2025-03-18HEBEI GELLEC NEW ENERGY MATERIAL SCI&TECHNOLOY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411829650.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing lithium-ion battery separators have insufficient performance improvement under high film breaking temperature and high performance requirements. The poor adhesion and stacking density of ceramic coatings have limited improvement in heat resistance.

Method used

Organic polyimide fibers are used as the separator material, and a slurry of polyimide (PI), organic supramolecular, carboxymethylcellulose and polymethylmethacrylate are coated on the base film to form a high-performance separator.

Benefits of technology

It achieves the improvement of high ionic conductivity, tensile strength and film rupture temperature, while reducing the friction coefficient, enhancing the adhesive performance, and meeting the requirements of high performance and high heat resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119651042A_ABST
    Figure CN119651042A_ABST
Patent Text Reader

Abstract

The invention discloses an organic polyimide fiber lithium ion battery diaphragm and a preparation method and application thereof.The organic polyimide fiber lithium ion battery diaphragm comprises a base membrane and a coating on the base membrane, and the coating comprises polyimide, organic supramolecules, carboxymethyl cellulose and polymethyl methacrylate according to the mass fraction, the ratio of the polyimide to the organic supramolecules to the carboxymethyl cellulose to the polymethyl methacrylate is 20: (1-2): 1: 2, and the number-average molecular weight of the polyimide is 32132-34227 g / mol. The organic polyimide fiber lithium ion battery diaphragm has the advantages of high ionic conductivity, high tensile strength, high diaphragm rupture temperature and low friction coefficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery separators, and in particular relates to an organic polyimide fiber lithium ion battery separator and a preparation method and application thereof. Background Art

[0002] As the charging rate of new energy vehicles becomes faster and faster, the high voltage and high current charging schemes they rely on have higher and higher requirements for high membrane rupture temperature and high performance of lithium-ion battery separators. Although the existing ceramic coating can improve the heat resistance of the separator, it is limited by the stacking density and stacking height, which limits the improvement of the membrane rupture temperature of the separator. Moreover, the ceramic itself cannot be bonded to the base film, and it is now generally used to increase the peel strength by adding adhesives. The use of ceramic coated separators has many of the above limitations.

[0003] In this situation, polyimide coated diaphragms came into being. As a fiber material with a high thermal decomposition temperature, polyimide can enhance the membrane rupture temperature of the diaphragm. Due to its extremely strong chemical stability, polyimide makes the diaphragm prepared by it have good corrosion resistance. However, the performance of polyimide coated diaphragms in the prior art needs to be further improved. For example, patent CN118315761A only mentions polyimide as a polymer diaphragm material layer, which is just a simple description of the diaphragm preparation process, and does not explain the improvement of diaphragm performance by adding polyimide from the perspective of monomer purification and polymerization. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention aims to provide an organic polyimide fiber lithium ion battery separator.

[0005] Another object of the present invention is to provide a method for preparing the organic polyimide fiber lithium ion battery separator.

[0006] Another object of the present invention is to provide a slurry.

[0007] The purpose of the present invention is achieved through the following technical solutions.

[0008] An organic polyimide fiber lithium ion battery separator comprises: a base film and a coating on the base film, wherein the coating comprises: polyimide (PI), organic supramolecules, carboxymethyl cellulose and polymethyl methacrylate, wherein the ratio of polyimide (PI), organic supramolecules, carboxymethyl cellulose and polymethyl methacrylate is 20:(1-2):1:2 by weight, the number average molecular weight of polyimide (PI) is 32132-34227 g / mol, and the structural formula of polyimide (PI) is:

[0009] The degree of polymerization n is 48 to 51. The method for obtaining the organic supramolecular comprises: using resorcinol and 1,3-bis(1,3-dioxycycloalkane-2-yl)propane as substrates, n-propanol as solvent, and morpholine as template agent, obtaining an organic supramolecular precursor under the catalysis of hydrochloric acid, purifying, and drying to obtain the organic supramolecular. Calculated by the amount of substance, the ratio of resorcinol, 1,3-bis(1,3-dioxycycloalkane-2-yl)propane and morpholine is 4:(1 to 2):(0.01 to 0.02).

[0010] In the above technical solution, polyimide (PI) is formed by polycondensation of a first substance and a second substance, the first substance is an A monomer with a purity of 99.4-99.6%, and the A monomer is 4-amino-N-(4-aminophenyl)-2-(trifluoromethyl)benzamide;

[0011] The second substance is a B monomer with a purity of 99.3-99.5%, and the B monomer is 6-(1,3-dioxo-1,3-dihydroisobenzofuran-5-yl)-4-(trifluoromethyl)phthalic anhydride.

[0012] In the above technical scheme, the method for obtaining polyimide (PI) includes: mixing the first substance, the second substance and the first solvent, performing a condensation reaction at 0-5°C for 8-10 hours to obtain a precursor polyamic acid, adding an imidization catalyst, performing an imidization reaction at 80-85°C for 8-10 hours, washing, and drying to obtain polyimide (PI), wherein, in terms of the amount of the substances, the ratio of the A monomer in the first substance, the B monomer in the second substance and the imidization catalyst is 1: (1.00-1.05): 0.11.

[0013] In the above technical solution, the A monomer with a purity of 80 to 94.3% is purified by gradient recrystallization of a low-polarity organic solvent to obtain the first substance, and the B monomer with a purity of 90 to 95.3% is purified by high-temperature melt crystallization to obtain the second substance.

[0014] In the above technical scheme, the method for obtaining the first substance (gradient recrystallization) includes: mixing a low-polarity organic solvent and a monomer A to be purified, stirring at room temperature for 30 to 60 minutes, heating to 77 to 78°C, reflux at 77 to 78°C for 30 to 60 minutes, cooling to 60 to 61°C, maintaining at 60 to 61°C for 30 to 60 minutes, cooling to 40 to 41°C, maintaining at 40 to 41°C for 1 to 2 hours, cooling to room temperature, filtering, and drying to obtain the first substance, wherein the monomer A to be purified is the monomer A with a purity of 80 to 94.3%, and the ratio of the volume fraction of the low-polarity organic solvent to the mass fraction of the monomer A to be purified is 1:(0.17 to 0.18), the unit of the volume fraction is L, and the unit of the mass fraction is kg.

[0015] In the above technical scheme, the method for obtaining the second substance is: adding the B monomer with a purity of 90-95.3% to a melt crystallizer, first heating to 190-191°C at a rate of 2-3°C / min, then heating to 195-196°C at a rate of 0.2-0.3°C / min, and maintaining at 195-196°C for 1-1.5 hours, cooling to 190-191°C at a rate of 0.1-0.2°C / min, and then cooling to 189°C at a rate of 0.05-0.1°C / min (crystals begin to slowly precipitate at 189°C), and cooling to 160-161°C at a rate of 9-15°C / h to obtain the second substance.

[0016] In the above technical solution, the imidization catalyst is a mixture of phthalic anhydride and isoquinoline.

[0017] In the above technical solution, the first solvent is N-methylpyrrolidone (NMP) (water content ≤ 2000 ppm) or N,N-dimethylacetamide (DMAC) (water content ≤ 2000 ppm), and the ratio of the volume fraction of the first solvent to the amount fraction of the substance of the A monomer in the first substance is 1: (1 to 1.1), the unit of the volume fraction is L, and the unit of the amount fraction of the substance is mol.

[0018] In the method for obtaining the first substance, the low-polarity organic solvent is ethyl acetate, and the water content of ethyl acetate is ≤2000ppm.

[0019] In the method for obtaining the organic supramolecule, the ratio of the volume fraction of n-propanol to the substance amount fraction of resorcinol is 1:(4-4.5), the unit of the volume fraction is L, and the unit of the substance amount fraction is mol.

[0020] In the above technical scheme, the method for obtaining the organic supramolecule is specifically as follows: n-propanol, resorcinol, 1,3-bis(1,3-dioxacycloalkane-2-yl)propane and morpholine are mixed, stirred at 0-5°C for 1-2h until uniform, hydrochloric acid is added, stirring is continued at 0-5°C for 1-2h, heated to 100-105°C and reacted at 100-105°C for 48-64h to obtain an organic supramolecule precursor, purified, dried, and obtained an organic supramolecule.

[0021] In the method for obtaining the organic supramolecule, the ratio of the volume fraction of hydrochloric acid to the substance amount fraction of resorcinol is (0.81-0.85):16, the unit of the volume fraction is L, and the unit of the substance amount fraction is mol.

[0022] In the method for obtaining the organic supramolecule, the concentration of HCl in the hydrochloric acid is 10 to 12 mol / L.

[0023] The preparation method of the above-mentioned organic polyimide fiber lithium-ion battery separator comprises: coating the slurry on at least one side of the base film, drying so that the base film is bonded with the coating, and obtaining the organic polyimide fiber lithium-ion battery separator, wherein the slurry comprises: polyimide (PI), organic supramolecules, a second solvent, carboxymethyl cellulose and polymethyl methacrylate.

[0024] In the above technical solution, the second solvent is N-methylpyrrolidone (NMP) (water content ≤ 2000 ppm) or N,N-dimethylformamide (DMF) (water content ≤ 2000 ppm).

[0025] In the above technical solution, the coating method is gravure roller coating or matrix dot coating.

[0026] A slurry comprises: polyimide (PI), organic supramolecule, a second solvent, carboxymethyl cellulose and polymethyl methacrylate, wherein the ratio of polyimide (PI), organic supramolecule, carboxymethyl cellulose and polymethyl methacrylate is 20:(1-2):1:2 by weight.

[0027] In the above technical solution, the ratio of the volume fraction of the second solvent to the mass fraction of the carboxymethyl cellulose is 1:(0.05-0.055), the unit of the volume fraction is L, and the unit of the mass fraction is kg.

[0028] The method for preparing the slurry comprises: mixing polyimide (PI), organic supramolecules, a second solvent, carboxymethyl cellulose and polymethyl methacrylate until they are uniform to obtain slurry.

[0029] In the above technical solution, polyimide (PI), organic supramolecules, a second solvent, carboxymethyl cellulose and polymethyl methacrylate are mixed and stirred at a rotation speed of 1800 to 2000 r / min and a revolution speed of 30 to 40 r / min for 1 to 1.5 hours until uniform to obtain a slurry.

[0030] Application of polyimide (PI), organic supramolecular, carboxymethyl cellulose and polymethyl methacrylate to synergistically improve the ionic conductivity, tensile strength and / or bonding properties of separators.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The organic polyimide fiber lithium ion battery separator of the present invention has the advantages of high ionic conductivity, high tensile strength, high membrane breaking temperature and low friction coefficient. The side chain groups and organic supramolecules in polyimide (PI) increase the steric hindrance, and the multiple cavities of the organic supramolecules can facilitate the free shuttle of lithium ions, so that the ionic conductivity of the separator is excellent. The semi-trapezoidal structure and the presence of aromatic rings of polyimide (PI) itself make it have the characteristics of excellent thermodynamic and mechanical properties. In turn, the mechanical strength of the separator is excellent and the membrane breaking temperature becomes higher. Moreover, the physical and chemical stability of polyimide (PI) is high, and the structure is not easily destroyed, so that the friction coefficient of the coating is low. The organic supramolecule contains a large number of hydroxyl groups, which can enhance the intermolecular van der Waals force and form intermolecular hydrogen bonds, further enhancing the bonding performance of the organic polyimide fiber lithium ion battery separator. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 To obtain a reaction formula between a first substance and a second substance;

[0034] Figure 2 This is the reaction formula for synthesizing polyimide (PI). DETAILED DESCRIPTION

[0035] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0036] The molecular weight of 4-amino-N-(4-aminophenyl)-2-(trifluoromethyl)benzamide is 295.26.

[0037] The molecular weight of 6-(1,3-dioxo-1,3-dihydroisobenzofuran-5-yl)-4-(trifluoromethyl)phthalic anhydride is 379.22.

[0038] The molecular weight of resorcinol is 110.11.

[0039] The molecular weight of 1,3-bis(1,3-dioxacycloalkane-2-yl)propane is 188.25.

[0040] The hot press can pressurize up to 1000kg and heat to 80℃ regardless of the model.

[0041] Hot-pressed positive electrode sheet bonding strength: the size of the cut diaphragm is 25*150mm, and the size of the positive electrode sheet is 25*150mm; the temperature of the hot press is adjusted to 80℃ and the pressure is 1000KG, and the diaphragm and the positive electrode sheet are preheated for 1s and hot pressed for 1s using the hot press; the hot-pressed positive electrode sheet bonding strength is tested using an electronic tensile testing machine, and the diaphragm and the positive electrode sheet are peeled off until the stretching distance of the electronic tensile testing machine is 50mm, the speed of the electronic tensile testing machine is 300mm / min, the peeling degree is 180°, the hot-pressed positive electrode sheet bonding strength = peeling force divided by the stretching distance of the electronic tensile testing machine, peeling force: the average value of the force collected by the electronic tensile testing machine during the peeling process of the diaphragm and the positive electrode sheet, the hot-pressed positive electrode sheet bonding strength test is calculated based on the data with a stretching distance between 10 and 40mm, that is, the hot-pressed positive electrode sheet bonding strength = peeling force with a stretching distance between 10 and 40mm divided by 30mm. The positive electrode is ternary lithium nickel cobalt aluminum oxide (LiNi 0.8 Co 0.15 Al 0.05 O2) pole piece.

[0042] Hot-pressed negative electrode bonding strength: The test method is basically the same as the "hot-pressed positive electrode bonding strength", the difference is that the "positive electrode" is replaced by the "negative electrode", and the negative electrode is a carbon-based graphite electrode (carbon content 91%).

[0043] Friction coefficient: measured according to GB 10006-88 method.

[0044] Ionic conductivity: Determined according to GBT36363-2018 method. The test temperature is 40°C and the relative humidity is 45-50%.

[0045] The number average molecular weight of polyimide (PI) is determined according to (GB / T 31816-2015 Determination of molecular weight and distribution of water treatment agent polymers - Gel chromatography).

[0046] Film rupture temperature: measured in accordance with GB / T 36800.1-2018.

[0047] The base film is a wet-process polyethylene film with a thickness of 7.1 μm and an air permeability of 71 Sec / 100 ml (it should be noted that base films of other thicknesses may also be used).

[0048] Examples 1 to 3

[0049] A method for preparing a slurry comprises: mixing polyimide (PI), organic supramolecules, a second solvent, carboxymethyl cellulose and polymethyl methacrylate in a polymerization reactor (Zhenhong Chemical Machinery Co., Ltd.), stirring for 1 hour at a rotation speed of 2000 r / min and a revolution speed of 40 r / min until uniform, to obtain a slurry, wherein the second solvent is Y, the ratio of polyimide (PI), organic supramolecules, carboxymethyl cellulose and polymethyl methacrylate is X in terms of mass fraction, the ratio of the volume fraction of the second solvent to the mass fraction of the carboxymethyl cellulose is 1:0.05, the unit of the volume fraction is L, and the unit of the mass fraction is kg.

[0050] like Figure 2 As shown, the method for obtaining polyimide (PI) is as follows: adding a first substance, a second substance and a first solvent into a polymerization reactor, performing polycondensation reaction at 0°C for 10 hours to obtain a precursor polyamic acid, adding an imidization catalyst, performing imidization reaction at 80°C for 8 hours, washing, and vacuum drying to obtain a powdered polyimide (PI) (number average molecular weight (Mn) of 34227 g / mol), wherein the first substance is an A monomer with a purity of 99.6%, and the A monomer is 4-amino-N-(4-aminophenyl)-2-(trifluoromethyl)benzamide, and the second substance is a B monomer with a purity of 99.5%, and the B monomer is 6-(1,3-dioxo-1, 3-dihydroisobenzofuran-5-yl)-4-(trifluoromethyl)phthalic anhydride, calculated by the amount of substance, the ratio of A monomer in the first substance, B monomer in the second substance and the imidization catalyst is 1:1.05:0.11, the imidization catalyst is a mixture of phthalic anhydride and isoquinoline (calculated by the amount of substance, the ratio of phthalic anhydride to isoquinoline is 0.1:0.01), the first solvent is N-methylpyrrolidone (NMP) (water content 1800ppm), the ratio of the volume fraction of the first solvent to the amount of substance fraction of A monomer in the first substance is 1:1, the unit of volume fraction is L, and the unit of amount of substance fraction is mol.

[0051] like Figure 1 As shown, the method for obtaining the first substance (gradient recrystallization) is: add 1L of ethyl acetate (water content 1800ppm) and 170g of the A monomer to be purified into a crystallizer, stir at room temperature for 30 minutes and then heat to 77°C, reflux at 77°C for 30 minutes, cool to 60°C at a rate of 0.5°C / min and maintain at 60°C for 0.5 hour, then cool to 40°C at a rate of 1°C / min and maintain at 40°C for 1 hour, finally cool to 25°C at a rate of 2°C / min, filter, and vacuum dry to obtain the first substance, wherein the A monomer to be purified is an A monomer with a purity of 94.3%.

[0052] like Figure 1As shown, the method for obtaining the second substance is: adding B monomer with a purity of 95.3% to a melt crystallizer, first heating to 191°C at a rate of 2°C / min, then heating to 195°C at a rate of 0.2°C / min and maintaining at 195°C for 1 hour, cooling to 190°C at a rate of 0.1°C / min, and then cooling to 189°C at a rate of 0.05°C / min. At 189°C, crystals begin to precipitate slowly. Cooling to 160°C at a rate of 9°C / h, scraping out the crystals after melt crystallization with a cooling rod scraper to obtain the second substance.

[0053] The method for obtaining the organic supramolecular is as follows: firstly, n-propanol is added into a synthesis reactor, and then resorcinol, 1,3-bis(1,3-dioxacycloalkane-2-yl)propane and morpholine are added, stirred at 0°C for 1 hour until uniform, hydrochloric acid (the concentration of HCl in the hydrochloric acid is 12 mol / L) is pumped in, stirring is continued at 0°C for 1 hour, heated to 100°C and reacted at 100°C for 48 hours to obtain an organic supramolecular precursor, purified (10 L CH3OH and the organic supramolecular precursor are mixed in a beaker, stirred uniformly, the turbid liquid in the beaker is poured into a centrifuge tube, centrifuged at a speed of 8000 r / min for 5 minutes, a powder is obtained at the bottom of the centrifuge tube, 1 L methanol is added to the powder, stirred, pulped and washed 4 times (30 minutes each time)), and vacuum dried to obtain a powdered organic supramolecular. Calculated by molar fractions, the ratio of resorcinol, 1,3-bis(1,3-dioxacycloalkane-2-yl)propane and morpholine is 4:1:0.01, the ratio of the volume fraction of hydrochloric acid to the volume fraction of resorcinol is 0.81:16, the unit of volume fraction is L, the unit of volume fraction is mol, the ratio of the volume fraction of n-propanol to the volume fraction of resorcinol is 1:4, the unit of volume fraction is L, and the unit of volume fraction is mol.

[0054] X and Y are shown in Table 1.

[0055] Table 1

[0056]

[0057] Example 4

[0058] A method for preparing a slurry comprises: mixing polyimide (PI), organic supramolecules, a second solvent, carboxymethyl cellulose and polymethyl methacrylate in a polymerization reactor (Zhenhong Chemical Machinery Co., Ltd.), stirring for 1.5 hours at a rotation speed of 1800 r / min and a revolution speed of 30 r / min until uniform, to obtain a slurry, wherein the second solvent is N-methylpyrrolidone (NMP) (water content 2000 ppm), the ratio of polyimide (PI), organic supramolecules, carboxymethyl cellulose and polymethyl methacrylate is 20:2:1:2 in terms of mass fraction, the ratio of the volume fraction of the second solvent to the mass fraction of the carboxymethyl cellulose is 1:0.05, the unit of the volume fraction is L, and the unit of the mass fraction is kg.

[0059] The method for obtaining polyimide (PI) is as follows: adding a first substance, a second substance and a first solvent into a polymerization reaction kettle, carrying out polycondensation reaction at 5°C for 8h to obtain a precursor polyamic acid, adding an imidization catalyst, carrying out imidization reaction at 85°C for 10 hours, washing, and vacuum drying to obtain a powdered polyimide (PI) (number average molecular weight (Mn) of 32132 g / mol), wherein the first substance is an A monomer with a purity of 99.4%, and the A monomer is 4-amino-N-(4-aminophenyl)-2-(trifluoromethyl)benzamide; the second substance is a B monomer with a purity of 99.3%, and the B monomer is 6-(1,3-dioxo-1,3-dihydro- isobenzofuran-5-yl)-4-(trifluoromethyl)phthalic anhydride, calculated by the amount of substance, the ratio of A monomer in the first substance, B monomer in the second substance and the imidization catalyst is 1:1.00:0.11, the imidization catalyst is a mixture of phthalic anhydride and isoquinoline (calculated by the amount of substance, the ratio of phthalic anhydride to isoquinoline is 0.1:0.01), the first solvent is N,N-dimethylacetamide (DMAC) (water content 1800ppm), the ratio of the volume fraction of the first solvent to the amount of substance fraction of A monomer in the first substance is 1:1.1, the unit of volume fraction is L, and the unit of amount of substance fraction is mol.

[0060] The method for obtaining the first substance (gradient recrystallization) is as follows: add 1L ethyl acetate (water content 2000ppm) and 180g of the A monomer to be purified to a crystallizer, stir at room temperature for 60 minutes, heat to 78°C, reflux at 78°C for 60 minutes, cool to 61°C at a rate of 0.5°C / min and maintain at 61°C for 1 hour, then cool to 41°C at a rate of 1°C / min and maintain at 41°C for 2 hours, finally cool to 25°C at a rate of 2°C / min, filter, and vacuum dry to obtain the first substance. The A monomer to be purified is an A monomer with a purity of 80%.

[0061] The method for obtaining the second substance is as follows: adding B monomer with a purity of 90.0% to a melt crystallizer, first heating to 190°C at a rate of 3°C / min, then heating to 196°C at a rate of 0.3°C / min and maintaining at 196°C for 1.5 hours, cooling to 191°C at a rate of 0.2°C / min, and then cooling to 189°C at a rate of 0.1°C / min. At 189°C, crystals begin to precipitate slowly. Cooling to 160°C at a rate of 15°C / h, scraping out the crystals after melt crystallization with a cooling rod scraper, and obtaining the second substance.

[0062] The method for obtaining the organic supramolecular is as follows: firstly, n-propanol is added into a synthesis reactor, and then resorcinol, 1,3-bis(1,3-dioxacycloalkane-2-yl)propane and morpholine are added, and the mixture is stirred at 5°C for 2h until uniform, and hydrochloric acid (the concentration of HCl in the hydrochloric acid is 10mol / L) is pumped in, and stirring is continued at 5°C for 1h, and the mixture is heated to 105°C and reacted at 105°C for 64h to obtain an organic supramolecular precursor, and the organic supramolecular precursor is obtained by purification (mixing 10L CH3OH and the organic supramolecular precursor in a beaker, stirring uniformly, pouring the turbid liquid in the beaker into a centrifuge tube, and centrifuging at a speed of 8000r / min for 5 minutes to obtain a powder at the bottom of the centrifuge tube, and then 1L methanol is added to the powder, and the powder is stirred, beaten and washed 4 times (30 minutes each time)), and vacuum drying is performed to obtain a powdered organic supramolecular. Calculated by molar fractions, the ratio of resorcinol, 1,3-bis(1,3-dioxacycloalkane-2-yl)propane and morpholine is 4:1:0.02, the ratio of the volume fraction of hydrochloric acid to the volume fraction of resorcinol is 0.85:16, the unit of volume fraction is L, the unit of volume fraction is mol, the ratio of the volume fraction of n-propanol to the volume fraction of resorcinol is 1:4.5, the unit of volume fraction is L, and the unit of volume fraction is mol.

[0063] Example 5

[0064] A method for preparing an organic polyimide fiber lithium-ion battery separator comprises: pumping the slurry prepared in Example 1 into a gravure roller coating structure through a slurry pump, coating it on both sides on a base film, drying it, and obtaining a coating with a single-side thickness of 5 microns on the base film to obtain an organic polyimide fiber lithium-ion battery separator.

[0065] The ionic conductivity of the organic polyimide fiber lithium ion battery separator prepared in Example 5 is 1.98 mS / cm, the tensile strength (TD) is 570 MPa, the tensile strength (MD) is 520 MPa, the film breaking temperature is 185°C, and the friction coefficient is 0.08. The hot-pressed positive electrode sheet bonding strength is 15.9 N / m, and the hot-pressed negative electrode sheet bonding strength is 15.0 N / m.

[0066] Example 6

[0067] A method for preparing an organic polyimide fiber lithium-ion battery separator comprises: pumping the slurry prepared in Example 1 into a matrix dot coating structure through a slurry pump, coating on both sides of a base film, drying, and obtaining a coating with a single-side thickness of 5 microns on the base film to obtain an organic polyimide fiber lithium-ion battery separator. The dot coating points on the organic polyimide fiber lithium-ion battery separator are circular in shape, with a diameter of 380 μm, arranged in a matrix, and with a spacing of 500 μm.

[0068] The organic polyimide fiber lithium-ion battery separator prepared in Example 6 has an ionic conductivity of 1.93 mS / cm, a friction coefficient of 0.06, a hot-pressed positive electrode sheet bonding strength of 16.8 N / m, a hot-pressed negative electrode sheet bonding strength of 17.1 N / m, a tensile strength (TD) of 470 MPa, a tensile strength (MD) of 420 MPa, and a membrane rupture temperature of 165°C.

[0069] Example 7

[0070] A method for preparing an organic polyimide fiber lithium-ion battery separator comprises: pumping the slurry prepared in Example 3 into a gravure roller coating structure through a slurry pump, coating it on both sides on a base film, drying it, and obtaining a coating with a single-side thickness of 4 microns on the base film to obtain an organic polyimide fiber lithium-ion battery separator.

[0071] The organic polyimide fiber lithium-ion battery separator prepared in Example 7 has an ionic conductivity of 1.84 mS / cm, a tensile strength (TD) of 550 MPa, a tensile strength (MD) of 490 MPa, a membrane rupture temperature of 182°C, a friction coefficient of 0.05, a hot-pressed positive electrode sheet bonding strength of 13.5 N / m, and a hot-pressed negative electrode sheet bonding strength of 11.9 N / m.

[0072] Example 8

[0073] A method for preparing an organic polyimide fiber lithium-ion battery separator comprises: pumping the slurry prepared in Example 2 into a gravure roller coating structure through a slurry pump, coating it on both sides on a base film, drying it, and obtaining a coating with a single-side thickness of 5 microns on the base film to obtain an organic polyimide fiber lithium-ion battery separator.

[0074] The ionic conductivity of the organic polyimide fiber lithium ion battery separator prepared in Example 8 is 1.89 mS / cm, the tensile strength (TD) is 540 MPa, the tensile strength (MD) is 480 MPa, the film breaking temperature is 184°C, and the friction coefficient is 0.06. The hot-pressed positive electrode sheet bonding strength is 14.1 N / m, and the hot-pressed negative electrode sheet bonding strength is 12.7 N / m.

[0075] Example 9

[0076] A method for preparing an organic polyimide fiber lithium-ion battery separator comprises: pumping the slurry prepared in Example 4 into a gravure roller coating structure through a slurry pump, coating it on both sides on a base film, drying it, and obtaining a coating with a single-side thickness of 5 microns on the base film to obtain an organic polyimide fiber lithium-ion battery separator.

[0077] The ionic conductivity of the organic polyimide fiber lithium ion battery separator prepared in Example 9 is 1.88 mS / cm, the tensile strength (TD) is 550 MPa, the tensile strength (MD) is 498 MPa, the film breaking temperature is 180°C, and the friction coefficient is 0.09. The hot-pressed positive electrode sheet bonding strength is 14.1 N / m, and the hot-pressed negative electrode sheet bonding strength is 12.3 N / m.

[0078] Example 10

[0079] A method for preparing an organic polyimide fiber lithium-ion battery separator comprises: pumping the slurry prepared in Example 4 into a matrix dot coating structure through a slurry pump, coating on both sides of a base film, drying, and obtaining a coating with a single-side thickness of 5 microns on the base film to obtain an organic polyimide fiber lithium-ion battery separator. The dot coating points on the organic polyimide fiber lithium-ion battery separator are circular in shape, with a diameter of 380 μm, arranged in a matrix, and with a spacing of 500 μm.

[0080] The ionic conductivity of the organic polyimide fiber lithium-ion battery separator prepared in Example 10 is 1.83 mS / cm, the friction coefficient is 0.07, the hot-pressed positive electrode sheet bonding strength is 15.8 N / m, the hot-pressed negative electrode sheet bonding strength is 15.1 N / m, the tensile strength (TD) is 450 MPa, the tensile strength (MD) is 410 MPa, and the membrane rupture temperature is 163°C.

[0081] Comparative Example 1

[0082] A method for preparing a lithium-ion battery separator comprises: coating the slurry in comparative example 1 on a base film on one side by using a concave roller coating structure, drying, obtaining a PVDF coating with a single-side thickness of 4 microns on the base film, and obtaining a lithium-ion battery separator. The method for preparing the slurry in comparative example 1 comprises: mixing conventional PVDF (melting point 151° C., particle size D50=7 μm), N-methylpyrrolidone (NMP) (water content 1800 ppm), carboxymethyl cellulose and polymethyl methacrylate in a polymerization reactor (Zhenhong Chemical Machinery Co., Ltd.), stirring for 1 hour at a rotation speed of 2000 r / min and a revolution speed of 40 r / min until uniform, and obtaining a slurry, wherein, in terms of mass fractions, the ratio of conventional PVDF, carboxymethyl cellulose and polymethyl methacrylate is 22:1:2, the ratio of the volume fraction of NMP to the mass fraction of carboxymethyl cellulose is 1:0.05, the unit of volume fraction is L, and the unit of mass fraction is kg. Conventional PVDF is purchased from Sinochem Blue Sky FLUOROMATICS LIMITED.

[0083] The lithium-ion battery separator of Comparative Example 1 has an ion conductivity of 0.90 mS / cm, a tensile strength (TD) of 150 MPa, a tensile strength (MD) of 190 MPa, a film breaking temperature of 146°C, and a friction coefficient of 0.45. The hot-pressed positive electrode sheet bonding strength is 4.5 N / m, and the hot-pressed negative electrode sheet bonding strength is 3.8 N / m.

[0084] Comparative Example 2

[0085] A method for preparing a lithium-ion battery separator is basically the same as Example 5, except that the slurry is different. The method for preparing the slurry of Comparative Example 2 is: replace the "first substance" in Example 1 with "A monomer with a purity of 94.3%", and replace the "second substance" with "B monomer with a purity of 95.3%". That is, Comparative Example 2 is not purified and is used directly. The number average molecular weight (Mn) of PI obtained in Comparative Example 2 is 29689 g / mol.

[0086] The single-side coating thickness of the lithium-ion battery separator prepared in Comparative Example 2 is 4.5 microns, the ion conductivity of Comparative Example 2 is 1.48 mS / cm, the tensile strength (TD) is 370 MPa, the tensile strength (MD) is 320 MPa, the film breaking temperature is 170°C, and the friction coefficient is 0.15. The hot-pressed positive electrode sheet bonding strength is 9.2 N / m, and the hot-pressed negative electrode sheet bonding strength is 10.0 N / m.

[0087] Comparative Example 3

[0088] A method for preparing a lithium-ion battery separator is basically the same as Example 5, except that the slurry is different. The method for preparing the slurry of Comparative Example 3 is as follows: the "first substance" of the slurry in Example 5 is replaced by "4,4'-diaminodiphenyl ether (ODA)", and the "second substance" is replaced by "pyromellitic acid anhydride". Neither 4,4'-diaminodiphenyl ether (ODA) nor pyromellitic acid anhydride is purified, and the purity of 4,4'-diaminodiphenyl ether (ODA) is 80%, and the purity of pyromellitic acid anhydride is 90%. The number average molecular weight (Mn) of PI obtained in Comparative Example 3 is 28235 g / mol.

[0089] The single-side coating thickness of the lithium-ion battery separator prepared in Comparative Example 3 is 4 microns, the ion conductivity of Comparative Example 3 is 1.38 mS / cm, the tensile strength (TD) is 368 MPa, the tensile strength (MD) is 330 MPa, the film breaking temperature is 159°C, and the friction coefficient is 0.17. The hot-pressed positive electrode sheet bonding strength is 8.3 N / m, and the hot-pressed negative electrode sheet bonding strength is 5.2 N / m.

[0090] Comparative Example 4

[0091] A method for preparing a lithium ion battery separator is substantially the same as that of Example 5, except that a different slurry is used. The slurry of Comparative Example 4 is substantially the same as that of Example 5, except that no organic supramolecular compound is added to the slurry of Comparative Example 4. The ratio of polyimide (PI), carboxymethyl cellulose and polymethyl methacrylate is 20:1:2 by weight.

[0092] The single-side coating thickness of the lithium-ion battery separator prepared in Comparative Example 4 is 5 microns, the ion conductivity of Comparative Example 4 is 0.98 mS / cm, the tensile strength (TD) is 565 MPa, the tensile strength (MD) is 515 MPa, the film breaking temperature is 180°C, and the friction coefficient is 0.12. The hot-pressed positive electrode sheet bonding strength is 14.8 N / m, and the hot-pressed negative electrode sheet bonding strength is 13.9 N / m.

[0093] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. An organic polyimide fiber lithium ion battery separator, comprising: The base film and the coating on the base film include: polyimide, organic supramolecule, carboxymethyl cellulose and polymethyl methacrylate. The ratio of polyimide, organic supramolecule, carboxymethyl cellulose and polymethyl methacrylate is 20:(1-2):1:2 by weight, and the number average molecular weight of polyimide is 32000-35000 g / mol.

2. The organic polyimide fiber lithium ion battery separator according to claim 1, characterized in that: The polyimide is formed by condensation of a first substance and a second substance, wherein the first substance is an A monomer with a purity of 99.4 to 99.6%, and the A monomer is 4-amino-N-(4-aminophenyl)-2-(trifluoromethyl)benzamide; the second substance is a B monomer with a purity of 99.3 to 99.5%, and the B monomer is 6-(1,3-dioxo-1,3-dihydroisobenzofuran-5-yl)-4-(trifluoromethyl)phthalic anhydride.

3. The organic polyimide fiber lithium ion battery separator according to claim 2, characterized in that: The method for obtaining polyimide comprises: mixing the first substance, the second substance and the first solvent, carrying out a polycondensation reaction at 0 to 5° C. for 8 to 10 hours to obtain a precursor polyamic acid, adding an imidization catalyst, carrying out an imidization reaction at 80 to 85° C. for 8 to 10 hours, washing, and drying to obtain polyimide, wherein, in terms of the amount of the substances, the ratio of the A monomer in the first substance, the B monomer in the second substance and the imidization catalyst is 1: (1.00 to 1.05): 0.

11.

4. The organic polyimide fiber lithium ion battery separator according to claim 1, characterized in that: The method for obtaining the organic supramolecular comprises: using resorcinol and 1,3-bis(1,3-dioxycycloalkane-2-yl)propane as substrates, n-propanol as a solvent, and morpholine as a template agent, obtaining an organic supramolecular precursor under the catalysis of hydrochloric acid, purifying, and drying to obtain the organic supramolecular, wherein the ratio of resorcinol, 1,3-bis(1,3-dioxycycloalkane-2-yl)propane and morpholine is 4:(1-2):(0.01-0.02) in terms of the amount of the substances.

5. The organic polyimide fiber lithium ion battery separator according to claim 3, characterized in that: The imidization catalyst is a mixture of phthalic anhydride and isoquinoline.

6. The method for preparing the organic polyimide fiber lithium ion battery separator according to any one of claims 1 to 5, characterized in that: include: The slurry is coated on at least one side of the base film and dried to make the base film adhere with the coating to obtain an organic polyimide fiber lithium ion battery separator. The slurry includes: polyimide, organic supramolecules, a second solvent, carboxymethyl cellulose and polymethyl methacrylate.

7. A slurry, characterized in that: include: The polyimide, the organic supramolecule, the second solvent, the carboxymethyl cellulose and the polymethyl methacrylate are present in a ratio of 20:(1-2):1:2 based on weight fractions.

8. The method for preparing the slurry according to claim 7, characterized in that: include: The polyimide, the organic supramolecule, the second solvent, the carboxymethyl cellulose and the polymethyl methacrylate are mixed until uniform to obtain a slurry.

9. Application of polyimide, organic supramolecules, carboxymethyl cellulose and polymethyl methacrylate to synergistically improve the ionic conductivity of the separator.

10. Application of polyimide, organic supramolecular, carboxymethyl cellulose and polymethyl methacrylate to synergistically improve the tensile strength and / or bonding properties of separators.

Citation Information

Patent Citations

  • Ionic phosphine ligand and positive trivalent ruthenium complex and preparation and application thereof

    CN106588985A

  • Preparation method of compound containing bipyrazole ring and intermediate thereof

    CN111100165A

  • High-temperature-resistant, high-voltage-resistant and high-load adhesive for lithium ion battery and battery positive pole piece applying same

    CN113214779A

  • Lithium battery slurry coated diaphragm and preparation method and coating slurry thereof

    CN116487820A